Precipitation increase counteracts warming effects on plant and soil C:N:P stoichiometry in an alpine meadow - Shi, Lina; Lin, Zhenrong; Wei, Xiaoting; Peng, Cuoji; Yao, Zeying; Han, Bing; Xiao, Qing; Zhou, Huakun; Deng, Yanfang; Liu, Kesi; Shao, Xinqing (Frontiers in Plant Science, 2022)
Temperature and precipitation are expected to increase in the forthcoming decades in the northeastern Qinghai-Tibetan Plateau, with uncertain effects of their interaction on plant and soil carbon:nitrogen:phosphorus (C:N:P) stoichiometry in alpine ecosystems. A two-year field experiment was conducted to examine the effects of warming, precipitation increase, and their interaction on soil and plant C:N:P stoichiometry at functional groups and community level in an alpine meadow. Warming increased aboveground biomass of legumes and N:P ratios of grasses and community, but did not affect soil C:N:P stoichiometry. The piecewise structural equation model (SEM) indicated that the positive effect of warming on community N:P ratio was mainly resulted from its positive influence on the aboveground biomass of functional groups. Precipitation increase reduced C:N ratios of soil, grasses, and community, indicating the alleviation in soil N-limitation and the reduction in N use efficiency of plant. SEM also demonstrated the decisive role of grasses C:N:P stoichiometry on the response of community C:N:P stoichiometry to precipitation increase. The interaction of warming and precipitation increase did not alter plant community and soil, N:P and C:P ratios, which was resulting from their antagonistic effects. The stable soil and plant community C:N:P stoichiometry raised important implications that the effect of warming was offset by precipitation increase. Our study highlights the importance of considering the interaction between warming and precipitation increase when predicting the impacts of climate change on biogeochemical cycles in alpine meadow ecosystems.